2020
DOI: 10.1039/c9dt04752b
|View full text |Cite
|
Sign up to set email alerts
|

Increased photocurrent of CuWO4 photoanodes by modification with the oxide carbodiimide Sn2O(NCN)

Abstract: Tin(II) oxide carbodiimide is a novel prospective semiconductor material with a band gap of 2.1 eV and lies chemically between metal oxides and metal carbodiimides. We report on the photochemical properties of this oxide carbodiimide and apply the material to form a heterojunction with CuWO 4 thin films for photoelectrochemical (PEC) water oxidation. Mott-Schottky experiments reveal that the title compound is an n-type semiconductor with a flat-band potential of −0.03 V and, as such, the position of the valenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The less electronegative element N and its more covalent interaction with the metal orbitals as compared to the O 2p orbitals induce an upward shift of the valence band (VB) in such compounds, resulting in higher light absorption capability toward the wide visible range. 9 11 Domen et al have demonstrated a niobium-based oxynitride BaNbO 2 N photoanode with photoexcitation up to 740 nm. 12 It should be noted that different anion ordering will affect the band gap varying up to 0.6 eV, which was proven previously on the example of CaTaO 2 N. 13 The proper band edge positions of quaternary oxynitrides generally straddle the redox potential of water, thereby making them promising visible-light-induced photoelectrodes for overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…The less electronegative element N and its more covalent interaction with the metal orbitals as compared to the O 2p orbitals induce an upward shift of the valence band (VB) in such compounds, resulting in higher light absorption capability toward the wide visible range. 9 11 Domen et al have demonstrated a niobium-based oxynitride BaNbO 2 N photoanode with photoexcitation up to 740 nm. 12 It should be noted that different anion ordering will affect the band gap varying up to 0.6 eV, which was proven previously on the example of CaTaO 2 N. 13 The proper band edge positions of quaternary oxynitrides generally straddle the redox potential of water, thereby making them promising visible-light-induced photoelectrodes for overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…We chose the ternary oxide CuWO 4 which exhibits a narrower band gap than the current best-performing oxidic semiconductor BiVO 4 used for photoanodes. 48 Similar to the measurements on the WO 3 photoanodes, the fabricated thin films of CuWO 4 were evaluated for PEC water oxidation with respect to the following parameters: (i) sulfate vs phosphate electrolyte and (ii) Bi 2 O 2 NCN vs BiPO 4 . The summarized results of the LSV and CA presented in Figure 7 show that the in-situ -activated Bi 2 O 2 NCN outperforms BiPO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…CuWO 4 electrodes were prepared as in our previous work. 48 A 1.26 g portion of sodium tungstate dihydrate (Na 2 WO 4 ·2H 2 O, 99.9%, Acros Organics) was dissolved in 15 mL of deionized water, and 1 mL hydrogen peroxide (30%) was added to the tungstate solution. The latter was stirred for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[19] Recent studies of the tin oxide carbodiimide compounds Sn 2 O(CN 2 ) [20] and Sn 9 O 5 Cl 4 (CN 2 ) 2 [21] suggested the existence of some yet unknown tin oxide halides, which are reported in this work. Building upon band structures and photochemical properties previously reported for tin oxide carbodiimide compounds [20][21][22] we herein present the electronic band structure and electron localization function of Sn 7 O 4 Cl 6 , as calculated by density functional theory.…”
Section: Introductionmentioning
confidence: 99%